2011
DOI: 10.1102/1470-7330.2011.0001
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of multidrug resistance in cancer

Abstract: Primary intrinsic and/or acquired multidrug resistance (MDR) is the main obstacle to successful cancer treatment. Functional molecular imaging of MDR in cancer using single photon or positron emitters may be helpful to identify multidrug-resistant tumours and predict not only those patients who are resistant to treatment, with a clinically unfavourable prognosis, but also those who are susceptible to the development of drug toxicity or even certain tumours . Variations in the mdr1 gene product may directly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Although the prognosis and treatment of breast cancer continue to evolve, MDR in cancer is still frequently occurred and becomes the crucial obstacle to limit the effectiveness of clinical antitumor drug treatment (Saeki et al, 2005;Dizdarevic and Peters, 2011). It has been well known that the mechanisms and signal pathways of MDR is complicated and multifactorial, it potentially involved alterations in the expression of various proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis and treatment of breast cancer continue to evolve, MDR in cancer is still frequently occurred and becomes the crucial obstacle to limit the effectiveness of clinical antitumor drug treatment (Saeki et al, 2005;Dizdarevic and Peters, 2011). It has been well known that the mechanisms and signal pathways of MDR is complicated and multifactorial, it potentially involved alterations in the expression of various proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, 99m Tc-sestamibi is released much faster from thyroid than from parathyroid tissue, a pathophysiologic pattern possibly related to down-regulation in the parathyroid of the membrane-associated P-glycoprotein system related to multidrug resistance, a system for which 99m Tc-sestamibi is also a substrate. [58][59][60][61] This differential washout rate of 99m Tc-sestamibi from the thyroid relative to the parathyroid permits parathyroid scintigraphy to be performed with this single tracer, according to the so-called dual-phase 99m Tc-sestamibi acquisition protocol. As originally described by Taillefer et al, 54 planar imaging of the neck and thorax is acquired at 15 minutes, then 2-3 hours after the i.v.…”
Section: Parathyroid Scintigraphymentioning
confidence: 99%
“…Finally, the combination of single-photon emission computed tomography, positron emission tomography, and other imaging techniques with genetic data, guided by the findings of preclinical and clinical studies of MDR, may prove important for the selection of optimal treatments for patients who demonstrate particular MDR phenotypes (Dizdarevic and Peters, 2011).…”
Section: Assessment Of Mdr Statusmentioning
confidence: 99%
“…Positron emission tomography using [ 18 F]fluoroethyl compounds (Kawamura et al, 2011) and 99m Tc-hexakis-2-methoxyisobutylisonitrile scintigraphy (Dizdarevic and Peters, 2011) were used recently to assess the in vivo function of P-gp and BCRP, whereas another study suggested that MDR could be assessed by using a carbon nanotube-drug supramolecular nanocomposite electrochemical sensor, as demonstrated with sensitive and MDR K562 leukemia cells (Zhang et al, 2011a). Finally, the combination of single-photon emission computed tomography, positron emission tomography, and other imaging techniques with genetic data, guided by the findings of preclinical and clinical studies of MDR, may prove important for the selection of optimal treatments for patients who demonstrate particular MDR phenotypes (Dizdarevic and Peters, 2011).…”
Section: Assessment Of Mdr Statusmentioning
confidence: 99%